A Reduction and pH Dual‐Sensitive Polymeric Vector for Long‐Circulating and Tumor‐Targeted siRNA Delivery. (31st October 2014) - Li, Jingguo; Yu, Xingsu; Wang, Yong; Yuan, Yuanyuan; Xiao, Hong; Cheng, Du; Shuai, Xintao
<x xml:space="preserve">Abstract</x> A novel reduction and pH dual‐sensitive nonviral vector for long‐circulating and tumor‐targeted siRNA delivery is described. The nanomedicine is negatively charged at neutral pH of bloodstream whereas it is positively charged at lower pH of tumor tissue (ca. 6.8). Interlayer crosslinking with disulfide bonds stabilizes the nanomedicine during blood circulation and allows quick intracellular siRNA release after endocytosis. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>